2015
DOI: 10.1038/nutd.2015.33
|View full text |Cite
|
Sign up to set email alerts
|

Omentin-1 plasma levels and cholesterol metabolism in obese patients with diabetes mellitus type 1: impact of weight reduction

Abstract: Background:Omentin-1 is an anti-inflammatory adipokine produced preferentially by visceral adipose tissue. Plasma levels of omentin-1 are decreased in obesity and other insulin-resistant states. Insulin resistance contributes to the changes of cholesterol synthesis and absorption as well. The aim of this study was to characterise omentin-1 plasma levels in obese patients with diabetes mellitus type 1 during weight reduction, and to elucidate the relationship between cholesterol metabolism and omentin-1.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 29 publications
2
36
1
5
Order By: Relevance
“…Moreover, omentin-1 levels increased 6 months after laparoscopy sleeve gastrectomy and a continued increase of these levels remained during the 2-year follow-up [12]. Lesna et al [14] reported that omentin-1 levels were stable during an intervention with a hypocaloric diet for 4 weeks. Nevertheless, a significant increase in omentin-1 levels was detected for a further diabetic diet, during 11 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, omentin-1 levels increased 6 months after laparoscopy sleeve gastrectomy and a continued increase of these levels remained during the 2-year follow-up [12]. Lesna et al [14] reported that omentin-1 levels were stable during an intervention with a hypocaloric diet for 4 weeks. Nevertheless, a significant increase in omentin-1 levels was detected for a further diabetic diet, during 11 months.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have evaluated these different strategies on serum concentrations of omentin-1 such as bariatric surgery [11][12] and dietary interventions [13][14]. To date, the effects of these treatments that produce weight loss on the level of omentin-1 have been contradictory, showing both elevations and decreases in circulating serum levels.…”
Section: Introductionmentioning
confidence: 99%
“…The mean weight loss in this study was only 6 kg. After 6.5 kg of weight loss, Lesna et al [13] reported that omentin-1 levels were stable during an intervention with a hypocaloric diet of 1,200 kcal per day during 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated specifically the effect of bariatric surgery [10][11] on serum concentrations of omentin-1. On the contrary, the results of studies that have evaluated the effect of dietary interventions have shown unclear results [12][13]. In clinical practice with morbid obese subjects, biliopancreatic diversion (BPD) is used and it has shown improvement in insulin resistance and glucose metabolism in obese patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…Wyciągnięte wnioski sugerowały, że omentyna-1 może aktywować kinazę białkową aktywowaną 5'AMP, która działa jako silny inhibitor syntezy endogennego cholesterolu. Można więc przypuszczać, że omentyna-1 przyczynia się do regulacji syntezy cholesterolu za pośrednictwem poprzez zwiększenie aktywności kinazy białkowej aktywowanej 5'AMP [46]. Anoreksja i otyłość są chorobami metabolicznymi będącymi dwoma skrajnościami.…”
Section: Rola Omentyny W Cukrzycy I Innych Chorobach Metabolicznychunclassified